2000
DOI: 10.1207/s15327663jcp0902_5
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Modes of Self‐Construal: Dimensions of Connectedness–Separateness and Advertising Appeals to the Cultural and Gender‐Specific Self

Abstract: This research examines how variations in consumers’ connectedness–separateness (C–S) self‐schema, which refers to an individual's perceptions of others as an extension of self or of the self as distinct from others, may explain cultural and gender‐level persuasion effects. Results from a cross‐cultural experiment demonstrate that a connected advertising appeal stressing interdependence and togetherness results in more favorable brand attitudes among Chinese and women consumers than does a separated appeal stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
80
1
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 29 publications
6
80
1
1
Order By: Relevance
“…Similar1 y, research on gender often assumes traditional sex roles for women and men. Findings show that women across cultures prefer other-focused or altruistic appeals and men prefer self-focused or egoistic appeals (e.g., Andsager et al, 2002;Brunel & Nelson, 2000;Wang et al, 2000). Our research challenges these views.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Similar1 y, research on gender often assumes traditional sex roles for women and men. Findings show that women across cultures prefer other-focused or altruistic appeals and men prefer self-focused or egoistic appeals (e.g., Andsager et al, 2002;Brunel & Nelson, 2000;Wang et al, 2000). Our research challenges these views.…”
Section: Discussioncontrasting
confidence: 47%
“…These perceptions are often considered to be stable (Miller, 2001). Yet, Gardner, Gabriel, and Lee (1999) found that using priming techniques to shift the relative interdependence of self-construals increased United States individuals' sense of obligation to help others "in ways that were once be-'Appeals that focus on individuals' concerns (Lau-Gesk, 2003) have been referred to as individualistic (Andsager, Austin, & Pinkleton, 2002;Han & Shavitt, 1994;Shavitt et al, 1997;Zhang & Gelb, 1996), separated (Wang, Bristol, Mowen, & Chakraborty, 2000), or ego-focused (Aaker & Williams, 1998). Other-focused appeals have also been referred to as collectivist (Andsager et al, 2002;Han & Shavitt, 1994;Shavitt et al, 1997;Zhang & Gelb, 1996), connected (Wang et al, 2000), or interpersonally focused (Lau-Gesk, 2003).…”
mentioning
confidence: 99%
“…Kanagawa et al's (2001) data, for example, suggested that cultural differences may be more evident in selfconcept stability-flexibility than in the specific content of the self. Other research (e.g., Kashima et al, 1995;Wang et al, 2000) suggested that cultural differences are most readily seen along autonomy and agency dimensions, whereas a relational dimension reflects gender differences more than cultural differences. Cross et al (2000) recently distinguished between two types of interdependent self-construal: collectivism-based interdependence (in which the group or situation dictates behavior) and relational interdependence (in which the self is defined in terms of relationships with close others).…”
Section: Discussionmentioning
confidence: 98%
“…Previous research has shown that self-construal influences the perceived separateness or connectedness of self to others (Wang, Bristol, Mowen & Chakraborty, 2000). According to the procedural application effect of the SPI model (Kühnen et al, 2001), when self-construal, one kind or another, is made salient, the corresponding cognitive style is more likely to be activated and affect subsequent judgments.…”
Section: Discussionmentioning
confidence: 99%